Pembuatan dan Pelatihan Website Administrasi Desa Bukit Lingkar Kecamatan Batang Cenaku Kabupaten Indragiri Hulu - Roza Yulida; Rosnita Rosnita; Deby Kurnia; Yulia Andriani; Fanny Septya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
A website is a whole web page that contains enormous information contained in a domain. Information on the web is presented on a web page which is formed from a collection of text, graphics, images, sound, and video. The purpose of making a website is to facilitate an agency, organization, and so on in containing information that can be accessed by the public at large. With the development of information technology, Indragiri Hulu District, in general, Bukit Lingkar Village, can access and find out the expected information about the village. Therefore we tried to design a Village Administration Website which later on the website will contain information about the Village and Village information in Bukit Lingkar Village and provide community training on how to use the website. In the process of creating and training this website, there are several activities carried out such as training on creating websites for Kukerta students, training for village government administrators in managing the website to launching the website. This activity starts with a vulnerable time from July to August 2020.